2007
DOI: 10.1002/path.2152
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional upregulation and unmethylation of the promoter region of p16 in invasive basal cell carcinoma cells and partial co‐localization with the γ2 chain of laminin‐332

Abstract: Basal cell carcinoma cells show low proliferation rates at the invasive front and a concordant upregulation of the cdk-inhibitor p16, limiting proliferative capacity. Little is known about the mechanisms of p16 regulation in normal and malignant cells apart from that many transcription factors such as Ets1, Ets2, SP1, SP3, JunB and the polycomb protein Bmi1 have the potential to induce or repress p16 expression. Therefore, the aim of this study was to determine how p16 is regulated in basal cell carcinoma with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Cytoplasmic p16 is therefore associated with the depth of invasion of gastric cancer, by virtue of the fact that the distinction between early and advanced gastric cancer is based on the criterion of the depth of invasion of cancer cells. This finding is in agreement with that of another study, in which the authors concluded that the invasion of basal cell carcinoma was induced by p16 upregulation (in both the nucleus and cytoplasm) with the requirement of a functional p16/cyclin D/Rb pathway (25).…”
Section: ------------------------------------------------------------supporting
confidence: 83%
“…Cytoplasmic p16 is therefore associated with the depth of invasion of gastric cancer, by virtue of the fact that the distinction between early and advanced gastric cancer is based on the criterion of the depth of invasion of cancer cells. This finding is in agreement with that of another study, in which the authors concluded that the invasion of basal cell carcinoma was induced by p16 upregulation (in both the nucleus and cytoplasm) with the requirement of a functional p16/cyclin D/Rb pathway (25).…”
Section: ------------------------------------------------------------supporting
confidence: 83%
“…The p16 INK4a cyclin-dependent kinase inhibitor (CDKN2a) has been implicated in replicative senescence, the state of permanent growth arrest driven by cell divisions or constitutive Ras-Raf-MEK signaling (see 131134 for p16 INK4a reviews; Fig. 2).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…The results suggest that coexpression of laminin β3 and γ2 chains is involved in the aggressive phenotype of gastric cancer cells, resulting in the progression of disease. Previous immunohistochemical studies have shown significant coexpression of laminin β3 and γ2 chains in the cytoplasm of invading or budding tumor cells in colorectal carcinoma, lingual squamous cell carcinoma, hepatocellular carcinoma, and basal cell carcinoma of the skin (4,9,20,21). We have also reported overexpression of laminin β3 and γ2 chains in biliary cancer (3).…”
Section: Discussionmentioning
confidence: 71%